1983
DOI: 10.1038/hdy.1983.28
|View full text |Cite
|
Sign up to set email alerts
|

Gynodioecy in plantago lanceolata L. II Inheritance of three male sterility types

Abstract: SUMMARYInheritance of male sterility has been studied in Plantago lanceolata. Crosses between plants, obtained from a 50 m2 area, yielded the entire array of possible sex phenotypes. Emphasis is put on nuclear inheritance of two nuclear-cytoplasmically determined male sterility types. In both types multiple interacting genes are involved. For MS1 a combination of two recessive and three dominant male sterility genes is proposed, for M52 three recessives. These are minimum estimates as the exact numbers could n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 45 publications
5
91
0
Order By: Relevance
“…Van Damme (1983) suggested that male sterility is plastic in P lanceolata, and our results demonstrate this for some families. Low temperature enhances femaleness in many diclinous species (Chailakhyan & Khrianin, 1987).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Van Damme (1983) suggested that male sterility is plastic in P lanceolata, and our results demonstrate this for some families. Low temperature enhances femaleness in many diclinous species (Chailakhyan & Khrianin, 1987).…”
Section: Discussionsupporting
confidence: 58%
“…The flowering season in North Carolina extends from May through August. The species is protogynous, gynodioecious, and self-incompatible (Ross, 1973;van Damme, 1983).…”
Section: Study Speciesmentioning
confidence: 99%
“…This apparent contradiction may not be so surprising when one considers that there exists a genetically based physiological basis for pollen, and not ovule, sterility. Studies of numerous plant species have shown that pollen sterility often results from nuclear-cytoplasmic interactions (Kheyr-Pour, 1980;Van Damme, 1983;Kesseli & fain, 1984;Boutin a al., 1987). In several species a strong correlation of mitochondrial genotype with male sterility has implicated the plant mitoehondrial genome as a controlling factor in pollen development (Warmke & Lee, 1977;Pring & Levings, 1978;Forde & Leaver, 1980;Powling, 1981;Dixon & Leaver, 1982;Leaver & Gray, 1982).…”
Section: Two Pathways To Reproductive Isolationmentioning
confidence: 99%
“…The two best known examples of putative nuclear inheritance of male sterility, in Origanum vulgare L. (Lewis and Crowe, 1956) and in Plantago lanceolata L. (Ross, 1969) have now been shown to be nuclear-cytoplasmic (Kheyr Pour, 1980;van Damme, 1983). The original studies and conclusions were based on a very small number of plants: five plants for 0. vulgare (Lewis and Crowe, 1956) and four plants for P. lanceolata (Ross, 1969).…”
Section: Introductionmentioning
confidence: 99%